Design for Six Sigma+Lean Toolset Implementing Innovations Successfully - Staudter, Christian; Mollenhauer, Jens-Peter.; Renata, Renata; Roenpage, Olin.; Hugo, Clemens von.; Hamalides, Alexis; Lunau, Stephan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
The Toolset is a comprehensive collection of the relevant Design for Six Sigma+Lean tools, which are necessary for successfully implementing innovations. All tools are presented in a clear structure, providing a good overview of the methodology. The chronology of the listed tools corresponds to the procedure in a Design for Six Sigma+Lean development project with the stages Define, Measure, Analyze, Design, and Verify. Due to this unique structure by which tools can be found and applied quickly we created a book that facilitates project work in practical use enormously.
Foreword -- Define: Initiating the Project -- Scoping the Project -- Managing the Project -- Measure: Selecting Customers -- Collecting Customer Voices -- Specifying Customer Needs -- Analyze: Identifying Design Concept -- Optimizing Design Concept -- Reviewing the Capability of the Concept -- Design: Develop, Test and Optimize Detailed Design -- Reviewing the Performance Capability for the Target Production -- Developing and Optimizing Lean Process -- Verify: Preparing Implementation -- Implementing the Process -- Handing over the Process.
Keywords: Business; Industrial management; Management; Business and Management; Media Management; Innovation/Technology Management; Electronic books